Male Involvement in Reproductive, Maternal and Child Health Services: A Qualitative Study in Dhading District of Nepal - Bist, Bimal Singh; Sherchan, Lokendra B.; Basnet, Sonu; Neupane, Subash; Kakchapati, Sampurna; Kurpiel, Andrzej (Social Inquiry: Journal of Social Science Research, 2021)
This study attempts to explore the involvement of fathers of children under two years of age in Maternal and Child health care in the Dhading district of Nepal. Four focus groups discussions with 38 fathers were conducted. Six major themes emerged from the analysis as follows: Access to health facility; knowledge on ANC and PNC visits; helping the pregnant and lactating mother; family decision-making; male parent's preference of health facility and the male's suggestions on how to improve the health care system for MCH care. The results revealed that priority was given to faith healers for health services; male parents were less aware of the importance of ANC and PNC visits and that social stigma negatively impacts the help given to the pregnant and lactating mother. Most of the participants were helpful and supportive of their wives during pregnancy and lactating. The mistrust created by the unavailability of health workers in the health facility, long distances to the health facility with roads inaccessible to ambulances and a lack of human resources in the village were all reasons for home delivery. Involvement of the male in health care activities and providing them with health education opens a window of opportunity to help achieve Maternal and Child health-related goals.